REGULARITIES OF MORPHOLOGICAL TRANSFORMATIONS IN THE VAGINA OF EARLY FETUSES - Proniaiev, D.V.; Bulyk, R.Y.; Khmara, Т.V. (World of Medicine and Biology, 2019)
Vaginal pathology constitutes a considerable part from a general amount of congenital and acquired pathology of the reproductive organs, which is indicated in the works of leading world scientists. The study is devoted to the determination of the anatomical features of the vagina of the fetus at the beginning of the perinatal period. The terms of the formation of the longitudinal and transverse folds of the mucous membrane of the vagina, the visualization of the vaults, its canalization and the breakthrough of the hymen are set.
Keywords: vagina; fetus; anatomy; human